Sinteza poroznih materialov iz metakrilatov in vinilestrov - Turnšek, Marko (visokošolska dela, 2014)
Influences of reaction conditions on the structure of porous glycidyl methacrylate type polymer supports were studied. Glycidyl methacrylate was chosen as the main functional monomer due to availability and possibility of nucleophilic modifications of epoxy groups. We studied the influence of crosslinker ethylene glycol dimethacrylate and various porogenic solvents on the morphology of porous polymer supports. Porous polymer supports were subsequently functionalized with various amines and thiols. Furthermore, porous polymers were hypercrosslinked, with an aim of increasing specific surface area of polymers. Furthermore, high internal phase emulsions internal phase containing dissolved monomer were prepared. Divinyl adipate was chosen as monomer because it is a reactive difunctional vinyl ester that consists of two ester bonds which can undergo hydrolytic attack. Influences of different compositions of emulsions, different types of initiator, addition of solvents and reaction conditions on emulsion stability and morphology of prepared polymer supports were studied. Appropriate surfactants and solvent were chosen for the formations of stable emulsions. Thermal initiator was used for polymerisation of emulsions and the use of photochemical initiator was also studied. We also studied the size and the shape of droplets from emulsions being heated during the preparation and aging of emulsions. An increase in droplet size of 5 fold and with aging after 25 hours increase of 0.4 fold was achieved. Emulsion preparation without salt in aqueous phase which promotes Ostwald ripening and coalescence of emulsion droplets was further studied. Prepared divinyl adipate porous polymer supports were exposed to PBS buffer and sodium hydroxide with different concentrations for studying the rate of degradation and adequacy of these media for degradation. In the last part of the thesis work, emulsions with incorporated inorganic component namely aluminium oxide in the continuous phase, were prepared. Propoxylated trimethylolpropane triacrylate and methyl methacrylate were used as monomers. Influence of solvent, amount of water phase, surfactant and dispersing agent on emulsion stability and morphology were studied. Samples with open cellular structure were treated thermally after the polymerisation. At 1400° C the entire organic component was burned and only the inorganic component remained. The aluminium oxide, which was fused together by the high temperature formed a solid. These sintered materials obtained the initial morphology of the precursor polyHIPE.
Keywords: biodegradation; biorazgradnja; bulk polymerization; composite materials; doktorske disertacije; emulsions; emulzije; funkcionalizacija polimerov; kompozitni materiali; metakrilati; methacrylates; poliHIPE; polimeri; polimerizacija v masi; polyHIPE; polymers; porous ceramics; porozna keramika; vinil estri; vinyl esters